Oseltamivir and influenza-related complications in children: a retrospective cohort in primary care - Lee, J; Smith, M; Bankhead, C; Perera-Salazar, R; Kousoulis, A; Butler, C; Wang, K (European Respiratory Society, 2020)
Background: Influenza and influenza-like illness (ILI) place considerable burden on health care systems, especially during influenza epidemics and pandemics. During the 2009/10 H1N1 influenza pandemic, UK national guidelines recommended antiviral medications for patients presenting within 72 h of ILI onset. However, it is not clear whether antiviral treatment was associated with reductions in influenza-related complications.